Preconscious Personality of the main character in Aladdin Movie - Sitompul, Naomi (Media Antartika Indonesia, 2023)
This research aims to determine the preconscious personality of the main character in the film Aladdin. Researchers used qualitative descriptive methods in this research using primary and secondary data. Researchers used documentation techniques and literary analysis. There are several procedures in conducting this research, such as watching the film, identifying essential points related to the study, classifying the characters' personalities and preconscious personalities in the movie, identifying plot developments, and explaining the conclusions. Thus, the selection of this research title is based on a combination of personal interests, academic interests, and the potential impact that can be generated. Characters are imaginings that are relevant to us and our experiences, whether like ourselves or other people we know. This research 1. How is the subconscious state of the main character depicted in the film Aladdin? 2. How does the state of the subconscious affect the personality of the main character? The psychoanalytic used Sigmund Freud's theory. The research results show that Aladdin's subconscious personality in the film is shown as a kind, humble, steadfast, and generous character. According to data from this research, the main character's personality, Aladdin, is described because of the film's storyline, where Aladdin is placed in poverty and then gets lucky, thus producing a conflict in the character's subconscious.